The Strategies Reducing the Negative Externalities of Semi-trailer Truck Transportation in Eastern Economic Corridor Area - Senarak, Chalermpong (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 2 (2020): April-June 2020, 2020)
The rising demand for sea-container transportation in most developing countries escalates the number of semi-trailer trucks (STTs) on the road resulting in air pollution, road accident, and traffic congestion. To address these negative externalities, this study originally identified a set of traffic control strategies and adopted the ordered logit model to analyze its effectiveness in reducing the STTs’ externalities in Laem Chabang municipality where many large seaports are located. The existing literature was used as the reference to generate the relevant attributions used to develop a questionnaire survey randomly distributed to the respondents in five communities. Based on 414 responses, the immediate lane changing was ranked the first, followed by the violation of speed limit, and the unsafe parking, while the defect of vehicle, support equipment, and coupling device was ranked in the top five potential causes of STTs’ externalities. The ordered logit model revealed that the non-engineering strategies, especially legal enforcement and driving skill improvement, had a larger impact on the reduction of negative externalities caused by both drivers and their vehicles, while the engineering strategies, such as rumble strips, and automatic speed camera, tended to reduce only the driver-generated externalities. Keywords: Strategies, negative externalities, semi-trailer trucks, Eastern Economic Corridor, Laem Chabang municipality, ordered logit model